Weighted estimates for multilinear commutators of Marcinkiewicz integrals with bounded kernel - Wu, Jianglong; Liu, Qingguo (Український математичний журнал, 2014)
Let μΩ,b→ be a multilinear commutator generalized by the n-dimensional Marcinkiewicz integral with bounded kernel μ Ώ and let bj ∈OscexpLrj , 1 ≤ j ≤ m. We prove the following weighted inequalities for ω ∈ A ∞ and 0 < p < ∞: